Makna Kata “Dipotong” (ekkópto) Dalam Roma 11:22 - Tjong, Andrew Lucas; Binar, Sri (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2025)
The struggle over whether salvation can be lost or not is a topic that frequently attracts attention among Christians. In the view that salvation can be lost, one of the verses used is Romans 11:22, particularly the word